Na-alloy tailored 3D/0D metal halide heterostructures enabling efficient charge transfer for color-integrated white scintillators - Zhi Yang; Jiangtao Cui; Ying Sun; Jisong Yao; Shuang Yang; Jizhong Song (Nature Communications)
Abstract Lead-free halide perovskites featuring broad emissions have attracted increasing interest as X-ray imaging scintillators. Currently, the radioluminescence spectrum is primarily tuned by dopants and crystal fields, thus exploring a heterostructure manner to extensively modulate emission intensity and linewidth presents an exciting opportunity. Herein, we synthesize 3D/0D Cs2NaLuCl6/Cs3LuCl6(Sb) heterostructures via a Na-alloying strategy to tailor the spectral feature of scintillators. We find that type I heterostructure can promote the emission of 0D Cs3LuCl6(Sb) through charge transfer mechanism, as corroborated by the combination of energy band alignment, ultrafast transient dynamics, microscopic photoluminescence and electrical conductivity. As a result, 3D/0D scintillator exhibits a 1.8-times higher radioluminescence intensity than 0D scintillator. Meanwhile, featuring a spectrum-flat white emission, 3D/0D scintillator provides a balanced RGB output enabling to extend the dynamic range in color-integrated X-ray imaging. These findings provide insights into constructing metal halide heterostructures with efficient charge transfer, and advance the design and application of lead-free perovskites and their derivatives.